A propósito de um lagar de cera e da actividade dos cerieiros em Penafiel - Soeiro, Teresa (Portvgalia : Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da FLUP, 2018)
We report a vernacular beeswax press, which was identified at Cancelos (Sebolido, Penafiel), as well as the occupation of beeswax chandler during the Modern and Contemporary Eras. These professional chandlers held an essential role in collecting the combs from small farms, in purifying its wax and in subsequently marketing the beeswax both in bulk and processed into candles and ex-votos over the local and interregional trade channels.